A Study of Antihaemophilic Globulin (Factor VIII) Consumption - Sen, N. N; Denson, K. W. E; Biggs, Rosemary (Thrombosis and Haemostasis, 1965)
A study has been made of the rate of disappearance of factor VIII during the clotting of n Dr mal plasma samples and of samples deficient in factors V, VII, IX, X, XI and XII. The rate of disappearance (or consumption) of factor VIII was the same in the normal and factor VII deficient samples. Delayed disappearance of factor VIII was observed in samples deficient in factors V, IX, X, XI and XII. The significance of the findings to the theory of blood coagulation is discussed.